Complete genomic congruence but non‐monophyly of Cymodocea (Cymodoceaceae), a small group of seagrasses. Issue 1 (27th January 2014) - Petersen, Gitte; Seberg, Ole; Short, Frederick T.; Fortes, Miguel D.
Abstract: The Cymodoceaceae is a small family of five genera ( Amphibolis, Cymodocea, Halodule, Syringodium, Thalassodendron ) that are easily recognizable when reproductive organs are present. To test monophyly of the five genera and clarify relationships among them, a phylogenetic analysis was conducted on data from two plastid genes and four mitochondrial genes. Most extraordinarily, the two genomic data partitions are completely congruent with an incongruence length difference of zero. However, the molecular data show that Cymodocea is non‐monophyletic. The taxonomic consequences will be either to split Cymodocea into two genera, to merge all genera except Halodule, or to merge Syringodium with one or two species of Cymodocea . Though monophyly of Cymodocea is strongly contradicted, the necessary taxonomic changes should not be made until a more strongly supported resolution of some relationships has been attained, and a few critical species have been added to the phylogeny.